Imunopatogenesis Asma: [Immunopathogenesis of Asthma Bronchiale] - Resti Yudhawati; Desak Putu Agung Krisdanti (Jurnal Respirasi, 2017)
Asthma is a chronic inflammatory disease of the airways characterized by recurrent wheezing, shortness of breath, chest tightness and cough especially at night and or early morning. Airflow resistance in asthma were caused by changes in the airways include bronchoconstriction, airway edema, hyperresponsiveness and airway remodeling. The inflammatory response in asthma patients varies among individuals, whether it can be immediate or late (slow-type) response. Different types of cells are known to play role in this process, especially mast cells, eosinophils, T lymphocytes, macrophages, neutrophils and epithelial cells. Degranulation of mast cells in the airways release inflammatory mediators and various metabolites that directly lead to smooth muscle hypersponsive resulting in airway obstruction. While eosinophil cells, mast cells and lymphocytes associated with slow-type responses, will release various mediators including leukotriene, prostaglandins and a number of proinflammatory cytokines. Type 2 immune response in the lower respiratory tract is a central immunologic process in asthma. This type 2 immune response is mediated by Th2 cells of CD4 + and IgE. The CD4 + Th2 cell is characterized by the large amount of transacting T-cell-specific transcription factor GATA-3 and the secretion of type 2 cytokines (IL-4, IL-5, IL-9 and IL-13). Excessive type 2 cytokines in the lower airway will trigger IgE-mediated hypersensitivity, epithelial cell activation, inflammatory cell inflation mediation into the airways, and cause remodeling responses in the epithelium and subepithelial matrices. This inflammatory cascade of type 2 cytokines is the pathological basis of the main symptoms of asthma.